Clinical aspects, imaging features, and considerations on bisphosphonate-related osteonecrosis risk in a pediatric patient with osteogenesis imperfecta - Costa, Fábio Wildson Gurgel (2015)
Osteogenesis imperfecta (OI) is a rare hereditary condition caused by changes in collagen metabolism. It is classified into four types according to clinical, genetic, and radiological criteria. Clinically, bone fragility, short stature, blue sclerae, and locomotion difficulties may be observed in this disease. OI is often associated to severe dental problems, such as dentinogenesis imperfecta (DI) and malocclusions. Radiographically, affected teeth may have crowns with bulbous appearance, accentuated constriction in the cementoenamel junction, narrowed roots, large root canals due to defective dentin formation, and taurodontism (enlarged pulp chambers). There is no definitive cure, but bisphosphonate therapy is reported to improve bone quality; however, there is a potential risk of bisphosphonate-related osteonecrosis of the jaw. In this study we report a case of OI in a male pediatric patient with no family history of OI who was receiving ongoing treatment with intravenous perfusion of bisphosphonate and who required dental surgery. In addition, we discussed the clinical and imaging findings and briefly reviewed the literature.